Analisis Penerapan Projek Penguatan Profil Pelajar Pancasila dengan Pembuatan Batik Ecoprint pada Siswa Sekolah Dasar - Hidayati, Putri; Febriansah, Dimas; Manyolay, Tessa; Sari, Syafni Gustina (Darul Yasin Al Sys, 2024)
This research aims to analyze the implementation of the Pancasila student profile strengthening project in elementary school. The research is qualitative in nature, and data collection techniques include observation, interviews, and documentation. The strengthening of the Pancasila student profile is integrated into the P5 project-based learning, adapting to and aligning with the new independent curriculum implemented in the school. The positive impact of implementing the Pancasila student profile strengthening project is evident in the gradual improvement of students' attitudes, initially less favorable, towards positive moral values. The application of this project also yields benefits in designing programs that cultivate a high sense of concern among students, fostering care and love for the surrounding environment, fellow students, mutual cooperation, and collaboration. The P5 activity involves creating ecoprint batik using canvas tote bags as a medium. Ecoprint batik can be embraced as a lifestyle trend promoting environmental consciousness, as it utilizes leaves and flowers from nature without the use of any chemicals, contributing to the enhancement of local wisdom. The resulting product, eco-friendly batik fabric, carries added cultural value.